Development of Color Coding Media for the Development of Early Childhood English - Maghfiroh, Nur Lailatul; Zahro, Ianatuz; Siswono, Hendrik (Teaching, Learning, and Development, 2025)
This study aims to develop Color Coding media as an instructional tool to enhance the English language skills of children aged 5–6 years at a selected early childhood education center. The research employed a Research and Development (R&D) methodology using the ADDIE model, which includes five systematic stages: analysis, design, development, implementation, and evaluation. The participants were kindergarten-aged children, and data were gathered using validation instruments completed by subject-matter experts in content, media, and design, alongside student-based evaluation tools. The validation process yielded results indicating a "Very Worthwhile" classification from material experts (96%), media experts (84.16%), and design experts (95.71%), suggesting no major revisions were necessary. Product trials conducted with students resulted in an average score of 83.03%, categorizing the media as "Very Feasible." These outcomes suggest that Color Coding media holds strong potential as an innovative and effective tool for improving early childhood English language proficiency, particularly in letter recognition, early writing skills, and foundational vocabulary acquisition. The practical implications of this research support the integration of visual-based media into early language curricula, offering a playful and engaging learning experience for young learners.